Characterization of the Small Robotic Telescope Instrument and Implementation at ITERA Lampung Astronomical Observatory - Hakim L Malasan; Robiatul Muztaba; Aditya Abdillah Yusuf; Adhitya Oktaviandra; Mitra Djamal; Tulin Bedel; Peter Aniol (Pandawa Institute, 2025)
As time has passed, the technological advances used to run these telescope systems have become faster, more reliable, and more user-friendly. Institut Teknologi Sumatera (ITERA) has installed a small robotic telescope at the Meteorology–Climatology–Geophysics Observing Station in collaboration with an ASTELCO System. The telescope system is designed to make fully robotic observations and can operate in both interactive and unattended robotic modes. This study's primary focus is on the OZT-ALTS telescope robotic system with the optical system using triplet apochromatic lens technology manufactured by LZOS with a focal ratio of f/8 refractor design. The telescope mount is a German Equatorial (NTM-500 manufactured by ASTELCO) with a direct drive system with an absolute encoder, and it allows fully programmable tracking speeds with a typical slewing speed of 20°/sec and a tracking accuracy range of 0.3–1.0 arcsec. For the process of collecting moon observation images, we use Manta G-031B. The OZT-ALTS robotic telescope is now contributing to monitoring crescent moon observation and astronomical studies. This paper presents the scientific motivation behind the OZT-ALTS robotic telescope and the facility's specifications and unique features. Furthermore, we present to characterize the result of the hardware OZT-ALTS robotic telescope system to increase the mechanical and optical performance of the telescope system based on the in-situ test observations. Based on the result, setting the Gain on the camera at 3.5 e-/ADU is the limit for the CCD to produce good-quality output images by utilizing the entire dynamic range without saturation. We also present an example of the science we have performed with the OZT-ALTS robotic telescope. The OZT-ALTS can observe young crescent moon events in the daylight after implementing the CLAHE technique to enhance contrast objects. On the other hand, the OZT-ALTS can also observe WASP-16b and WASP-34b exoplanets by using the transit method to analyze the decreasing light curve when a planet passes between a star and its observer.